Synthesis and characterization of thermo-responsive ionic liquids (TRILs) - M. A. M, Abdullah; M. S., Man; Syamsul. Bahari, Abdullah; Syed Mohd Saufi, Tuan Chik (IOP Publishing, 2020)
Normally, an ionic liquids (ILs) is classified as hydrophilic or hydrophobic depending on its composition, whether it is miscible or immiscible with water. Nevertheless, this classification is ambiguous, since the miscibility of some ILs with water is strongly depending on temperature change. There are two classifications of thermo-responsive ionic liquids (TRILs) which are lower critical solution temperature (LCST) and upper critical solution temperature (UCST) behavior types. The aim of this study is to synthesis and characterize tetrafloroborate-based (BF4 −) anion with different alkyl chain of imidazolium- based cations ([Emim], [Bmim], [Hmim], [Omim]) and trifloroacetate (CFOO−) anion with different cations (ammonium, anilinium, pyridinium and phosphonium). The prepared ILs were mixed with water (30:70 wt %) and the resulting solutions were stirred vigorously for certain period of time. These solutions were cooled to 00C and then gradually heated to 70 0C. When the solution was found to be phase-separated upon heating, this mixture undergoes the LCST- type phase transition but its contrary with UCST behavioral. The TRILs were characterized using Fourier Transform Infrared (FTIR) to identify the functional group and Nuclear Magnetic Resonance (NMR) in confirming the structure. Due to the special property of TRILs that became phase separation by changing the temperature, it can be recovered easily and reused for many recycles in wide range of application.